THE FIRST RUSSIAN STRATEGIC STUDY OF PHARMACOTHERAPY FOR RHEUMATOID ARTHRITIS (REMARCA TRIAL): RESULTS OF 12-MONTH TREATMENT IN 130 PATIENTS - D. E. Karateev; E. L. Luchikhina; N. V. Demidova; G. S. Gridneva; M. A. Kanonirova; Yu. V. Muravyev; G. V. Lukina; Yu. A. Olyunin; K. A. Kasumova; E. N. Aleksandrova; A. A. Novikov; A. A. Avdeeva; et al. (Научно-практическая ревматология)
To introduce treat-to-target recommendations is an important task of modern rheumatology; however, there is still a diversity of serious problems relating to a scientific rationale and a clinical one for this strategy and to the possibilities of its implementation in real clinical practice, in the rheumatology service of the Russian Federation in particular, by taking into account the specific features of funding for high-tech medical care.Objective: to determine the efficiency and safety of combined therapy with subcutaneous methotrexate (MT) and biological agents (BA) when using the treat-to-target strategy in patients with active early and extended-stage rheumatoid arthritis (RA) who have risk factors for a poor prognosis.Subjects and methods.The results of the REMARCA (Russian InvEstigation of MethotrexAte and biologicals in eaRly aCtive inflammatory Arthritis) trial of 130 patients followed up for 12 months or more were given. There was a female preponderance; mean age 48.9±13.9 years, rheumatoid factor positivity (86.9%); anti-cyclic citrullinated peptide antibody positivity (89.2%). Seventy patients formed a subgroup of early RA (disease duration ≤6 months (mean 4.17±1.39 months)); 60 patients were a subgroup of advanced-stage RA (disease duration >6 months (mean 30.8±32.7 months)). In all the patients, therapy was initiated by using subcutaneous MT with its rapid dose escalation up to 20–30 mg/week and the achievement of the treatment goal (low disease activity or remission) was checked every 3 months and depending on the result a decision had been taken to add or not to add a biological agent (BA) (a tumor necrosis factor inhibitor or abatacept). If the former was insufficiently effective, it was substituted for a BA from another class.Results. Subcutaneous MT monotherapy provided remission or low disease activity in 49 (37.7%) patients; a BA was given to 81 (62.3%) patients. Following 6 and 12 months, low activity or remission according to SDAI was observed significantly more frequently in the patients who continued subcutaneous MT monotherapy than in those who received combined therapy with MT and BA. The similar results were obtained by using DAS28 and CDAI to assess a trend in disease activity. After 6- and 12-month follow-up, there was a significantly more marked decline of tender joint count, SDAI and CDAI in early RA than in advanced-stage RA; at 12 months, SDAI remission rate was 45.7% and 28.3%, respectively (p=0.047).Conclusion. The treat-to-target strategy should be used in real clinical practice and can yield spectacular results. Active therapy with subcutaneous MT with its rapid dose escalation to the maximally tolerable dose allows identification of a considerable group of patients (38%) with a good response to MT monotherapy